Thermally conductive silicone composition
By adding specific types and contents of organopolysiloxane, hydrophobic pyrolysis silica, thermal fillers and polyethers to the thermally conductive silicone composition, the problem that the thermally conductive silicone composition is difficult to maintain processingability and dispensability at low viscosity is solved, and high thermal conductivity and good shape retention are achieved.
Patent Information
- Application Number
- CN202280099999.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2022-10-10
- Publication Date
- 2025-04-25
AI Technical Summary
The existing thermally conductive silicone compositions are difficult to maintain handleability and dispensability at low viscosity and tend to slide off in a vertical position.
The viscosity and shape retention of the composition are improved by adjusting the content and structure of each component.
It achieves excellent handling and dispensability at low viscosity, while not slipping easily in a vertical position and maintaining high thermal conductivity.
Smart Images

Figure CN119894982A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a thermally conductive silicone composition which exhibits good shape retention properties and high thermal conductivity despite good handleability and dispensability. Background Art
[0002] Thermally conductive silicone compositions are widely used in various industries due to their unique properties, including excellent electrical insulation and excellent thermal stability, and are therefore used as thermally conductive silicone grease, thermally conductive silicone gel compositions, thermally conductive silicone rubber compositions, etc. in various applications, such as encapsulants or potting materials in electrical / electronic devices that may require higher temperatures. In specific applications, the thixotropic properties of the thermally conductive silicone composition are required so that the shape of the composition is maintained after the composition is dispensed. It is well known that the thixotropic properties of silicone compositions are generally obtained by adding fine fillers (such as hydrophobic fumed silica) or some types of organic liquid compounds with polar groups (such as silanol groups, epoxy groups, amine groups or polyether groups).
[0003] For example, Patent Document 1 discloses a silicone composition for preparing a cured silicone product, the composition comprising: an organopolysiloxane having an average of at least two alkenyl groups per molecule, an organopolysiloxane having an average of at least two silicon-bonded hydrogen atoms per molecule, an alumina filler, a polyether, and a hydrosilylation reaction catalyst.
[0004] Patent document 2 discloses a thermally conductive silicone composition comprising: an organopolysiloxane having a viscosity of at least 500 mPa·s at 25° C., a thermally conductive filler; fine silica powder, an organopolysiloxane represented by a specific general formula and having a viscosity of less than 500 mPa·s at 25° C., and a silane compound of the specific general formula.
[0005] Patent document 3 discloses a heat-curable thermally conductive silicone grease composition, which comprises: an organopolysiloxane having a viscosity of 100 mPa·s to 100,000 mPa·s at 25°C and having at least one alkenyl group per molecule, an organopolysiloxane having a specific general formula, an organopolysiloxane having at least two silicon-bonded hydrogen atoms per molecule, a catalyst selected from the group consisting of platinum and platinum compounds, a thermally conductive filler having a thermal conductivity of at least 10 W / m·°C, and finely divided silica.
[0006] Patent document 4 discloses a room-temperature storable, addition one-part, heat-curable thermally conductive silicone grease composition, the composition comprising: an organopolysiloxane having a viscosity of 50 to 100,000 mPa·s at 25°C and having at least one alkenyl group per molecule; a liquid organopolysiloxane having a viscosity of up to 100 mPa·s at 25°C, 2 to 10 Si-H groups per molecule, and at least one alkoxy and / or epoxy group bonded to a silicon atom via an alkylene group, the polysiloxane having a degree of polymerization of up to 15 and a skeleton containing a cyclic structure; a photoactive platinum complex curing catalyst; a thermally conductive filler having a thermal conductivity of at least 10 W / m·°C; an organopolysiloxane having a specific general formula; and finely divided silica.
[0007] Patent document 5 discloses a thermally conductive organopolysiloxane composition comprising: a thermally conductive filler, a siloxane compound represented by a specific general formula, an alkoxysilane compound represented by a specific general formula, an organopolysiloxane having one or more aliphatic unsaturated groups per molecule, an organopolysiloxane having two or more hydrogen atoms bonded to silicon atoms per molecule, a platinum-based catalyst, and optionally fumed silica chemically treated with a silazane compound.
[0008] However, if the viscosity of such thermally conductive silicone compositions is reduced in order to improve their handleability and dispensability, the coating begins to slide off after the coated surface has assumed a vertical position.
[0009] Prior art literature
[0010] Patent Literature
[0011] Patent Document 1: U.S. Patent No. 6,448,329A
[0012] Patent Document 2: U.S. Patent Application Publication No. 2011 / 0188213A1
[0013] Patent Document 3: U.S. Patent Application Publication No. 2015 / 0148273A1
[0014] Patent Document 4: U.S. Patent Application Publication No. 2019 / 0085167A1
[0015] Patent Document 5: U.S. Patent Application Publication No. 2020 / 0140736A1 Summary of the invention
[0016] Technical issues
[0017] The object of the present invention is to provide a thermally conductive silicone composition which has excellent handleability and dispensability at a low viscosity and which, after being applied to a surface, does not collapse over time and does not experience sliding even when this surface assumes a vertical position.
[0018] Solution to the problem
[0019] The thermally conductive silicone composition of the present invention comprises:
[0020] (A) an organopolysiloxane having at least one alkenyl group having 2 to 12 carbon atoms per molecule and having a viscosity at 25° C. of 10 to 10,000 mPa·s;
[0021] (B) hydrophobic fumed silica;
[0022] (C) at least one thermally conductive filler; and
[0023] (D) at least one polyether selected from the group consisting of: (D1) polytetramethylene ether glycol, (D2) alcohol-initiated copolymers of ethylene oxide and propylene oxide, and (D3)
[0024] Polyether-modified organopolysiloxane,
[0025] wherein the content of component (A) is in the range of 0.5% by mass to 5% by mass, the content of component (B) is in the range of 0.01% by mass to 0.5% by mass, the content of component (C) is at least 90% by mass, and the content of component (D) is in the range of 0.05% by mass to 5% by mass, respectively, relative to the total amount of the composition.
[0026] In various embodiments, component (D1) is generally a polytetramethylene ether glycol represented by the following general formula:
[0027] H-(OCH2CH2CH2CH2) m –OH
[0028] wherein m is an appropriate number giving the polytetramethylene ether glycol a molecular weight of a number average molecular weight (Mn) of 300 to 3,000 as measured by gel permeation chromatography.
[0029] In various embodiments, component (D2) is typically an alcohol-initiated copolymer of ethylene oxide and propylene oxide containing from 50 to 99 mass % of propylene oxide units in the copolymer.
[0030] In various embodiments, component (D3) is typically a polyether-modified organopolysiloxane selected from polyether-grafted organopolysiloxanes or block copolymers of polyethers and organopolysiloxanes.
[0031] In various embodiments, the thermally conductive silicone composition may further include: (E) an organopolysiloxane having at least two silicon-bonded hydrogen atoms per molecule, the organopolysiloxane being present in an amount such that the silicon-bonded hydrogen atoms in component (E) are 0.1 mol to 5 mol per 1 mol of alkenyl groups in component (A); and (F) a hydrosilylation reaction catalyst in an amount sufficient to promote curing of the composition.
[0032] In various embodiments, the thermally conductive silicone composition may further include: (G) a hydrosilylation reaction inhibitor in an amount sufficient to control the curing speed of the composition.
[0033] In various embodiments, the thermally conductive silicone composition may further include: (H) a filler treating agent in an amount sufficient to treat component (C).
[0034] In various embodiments, the thermally conductive silicone composition may further comprise: (I) a pigment in an amount sufficient to maintain the desired physical properties of the composition.
[0035] Effects of the Invention
[0036] The thermally conductive silicone composition of the present invention exhibits good shape retention properties and high thermal conductivity despite good handleability and dispensability. BRIEF DESCRIPTION OF THE DRAWINGS
[0037] Figure 1 This is a schematic photo of the long tail observation test.
[0038] Figure 2 It is a schematic diagram of aspect ratio (AR) obtained at the initial stage and after 24 hours of input.
[0039] Figure 3 This is a schematic photo of the collapse resistance test.
[0040] Figure 4 This is a schematic photo of the vertical retention test.
[0041] definition
[0042] The term "comprising" or "containing" is used in its broadest sense herein, meaning and encompassing the concepts of "including", "consisting essentially of" and "consisting of". The use of "for example", "for example", "such as" and "including" to list illustrative examples is not meant to be limited to the listed examples. Therefore, "for example" or "such as" means "for example, but not limited to" or "such as, but not limited to" and encompasses other similar or equivalent examples. As used herein, the term "about" is used to reasonably encompass or describe minor variations of numerical values measured by instrumental analysis or as a result of sample processing. Such minor variations can be approximately ±0-25, ±0-10, ±0-5 or ±0-2.5% of a numerical value. In addition, the term "about" is applicable to two numerical values when associated with a range of values. In addition, the term "about" is applicable to numerical values even when not explicitly stated.
[0043] It should be understood that the appended claims are not limited to the specific and particular compounds, compositions or methods described in the detailed description, which may vary between specific embodiments falling within the scope of the appended claims. With respect to any Markush group relied upon herein to describe specific features or aspects of various embodiments, it should be understood that different, special and / or unexpected results may be obtained from each member of the corresponding Markush group independent of all other Markush members. Each member of the Markush group may be relied upon individually and / or in combination and provides adequate support for specific embodiments within the scope of the appended claims.
[0044] It should also be understood that any ranges and sub-ranges relied upon in describing various embodiments of the present invention fall within the scope of the appended claims independently and collectively, and should be understood to describe and contemplate all ranges including integer values and / or fractional values therein, even if such values are not explicitly written herein. It will be readily appreciated by those skilled in the art that the enumerated ranges and sub-ranges fully describe and enable various embodiments of the present invention, and such ranges and sub-ranges may be further delineated as related halves, thirds, quarters, fifths, etc. As just one example, the range of "0.1 to 0.9" may be further delineated as the lower third (i.e., 0.1 to 0.3), the middle third (i.e., 0.4 to 0.6), and the upper third (i.e., 0.7 to 0.9), which are individually and collectively within the scope of the appended claims, and may be individually and / or collectively relied upon and provide sufficient support for specific embodiments within the scope of the appended claims. In addition, with respect to language such as "at least," "greater than," "less than," "not exceeding," etc., which limits or modifies a range, it should be understood that such language includes sub-ranges and / or upper or lower limits. As another example, a range of "at least 10" essentially includes a subrange of at least 10 to 35, a subrange of at least 10 to 25, a subrange of 25 to 35, etc., and each subrange can be relied upon individually and / or collectively and provide sufficient support for specific embodiments within the scope of the appended claims. Finally, independent numerical values within the disclosed ranges can be relied upon and provide sufficient support for specific embodiments within the scope of the appended claims. For example, a range of "1 to 9" includes individual integers such as 3, and individual numbers including decimal points (or fractions) such as 4.1, which can be relied upon and provide sufficient support for specific embodiments within the scope of the appended claims. DETAILED DESCRIPTION
[0045] The thermally conductive silicone composition of the present invention will be explained in detail.
[0046] Component (A) is a main component in the composition and is an organopolysiloxane having at least two alkenyl groups having 2 to 12 carbon atoms per molecule. Examples of alkenyl groups include vinyl groups, allyl groups, butenyl groups, pentenyl groups, hexenyl groups, heptenyl groups, octenyl groups, nonenyl groups, decenyl groups, undecenyl groups and dodecenyl groups, wherein vinyl groups are preferred. In addition, in addition to alkenyl groups, examples of groups bonded to silicon atoms in component (A) include alkyl groups with 1 to 12 carbon atoms, such as methyl groups, ethyl groups, propyl groups, isopropyl groups, butyl groups, isobutyl groups, tert-butyl groups, pentyl groups, neopentyl groups, hexyl groups, cyclohexyl groups, heptyl groups, octyl groups, nonyl groups, decyl groups, undecyl groups and dodecyl groups; aryl groups with 6 to 12 carbon atoms, such as phenyl groups, tolyl groups, xylyl groups and naphthyl groups; aralkyl groups with 7 to 12 carbon atoms, such as benzyl groups, phenethyl groups and phenylpropyl groups; and groups in which some or all of the hydrogen atoms in these groups are replaced by halogen atoms such as fluorine atoms, chlorine atoms or bromine atoms. In addition, the silicon atoms in component (A) may also have a small amount of hydroxyl groups or alkoxy groups, such as methoxy groups or ethoxy groups, within the range of not damaging the object of the present invention. However, the organopolysiloxane of component (A) does not have a polyether group in the molecule.
[0047] Examples of the molecular structure of component (A) include a linear structure, a partially branched linear structure, a branched structure, a cyclic structure, and a three-dimensional network structure. Component (A) may be one type of organopolysiloxane having these molecular structures, or may be a mixture of two or more types of organopolysiloxanes having these molecular structures.
[0048] Examples of component (A) include dimethylpolysiloxanes having both molecular ends capped with dimethylvinylsiloxy groups; copolymers of dimethylsiloxane and methylvinylsiloxane having both molecular ends capped with trimethylsiloxy groups; copolymers of dimethylsiloxane and methylvinylsiloxane having both molecular ends capped with dimethylvinylsiloxy groups; copolymers of dimethylsiloxane, methylphenylsiloxane and methylvinylsiloxane having both molecular ends capped with trimethylsiloxy groups; copolymers of dimethylsiloxane and methylvinylsiloxane having both molecular ends capped with silanol groups; and siloxane units represented by the formula: (CH3)3SiO 1 / 2 , Siloxane units represented by the formula: (CH3)2(CH2=CH)SiO 1 / 2 、Through formula CH3SiO 3 / 2 The siloxane unit represented by the formula: (CH3)2SiO2 / 2 An organopolysiloxane composed of:
[0049] In addition, the viscosity of component (A) at 25°C is in the range of 10mPa·s to 10,000mPa·s, preferably in the range of 10mPa·s to 5,000mPa·s, alternatively in the range of 10mPa·s to 3,000mPa·s, or alternatively in the range of 50mPa·s to 2,000mPa·s. This is because when the viscosity of component (A) is greater than or equal to the lower limit of the above range, the mechanical properties of the cured product of the composition are improved, and when the viscosity of component (A) is less than or equal to the upper limit of the above range, the handling of the composition is improved. It should be noted that in this specification, the viscosity at 25°C is a value measured using a rheometer according to ASTM D 1084.
[0050] The content of component (A) is in the range of 0.5% by mass to 5% by mass relative to the total amount of the composition. This is because when the content of component (A) is greater than or equal to the lower limit of the above range, the processability of the composition is improved, and when the content of component (A) is less than or equal to the upper limit of the above range, the thermal conductivity of the composition is improved.
[0051] Component (B) is hydrophobic fumed silica, preferably with a BET specific surface area of 100 m 2 / g to 400m 2 / g, alternatively 150m 2 / g to 400m 2 / g, or alternatively 200m 2 / g to 400m 2 This is because when the BET specific surface area of the fumed silica is within the above range, the thixotropic property of the composition is improved.
[0052] The content of component (B) is 0.01% to about 0.5% by mass, preferably 0.01% to about 0.1% by mass, relative to the total weight of the composition. This is because when the content of component (B) is greater than or equal to the lower limit of the above range, the thixotropic property of the composition is improved, and when the content of component (B) is less than or equal to the upper limit of the above range, the handleability and dispensability of the composition are improved.
[0053] Component (C) is at least one thermally conductive filler. For example, component (C) can be any thermally conductive filler selected from metal, alloy, non-metal, metal oxide, metal hydrate or ceramic or any combination of more than one thermally conductive filler. Exemplary metals include but are not limited to aluminum, copper, silver, zinc, nickel, tin, indium and lead. Exemplary non-metals include but are not limited to carbon, graphite, diamond, carbon nanotubes, carbon fiber, graphene, silicon carbide and silicon nitride. Exemplary metal oxides, metal hydroxides and ceramics include but are not limited to aluminum oxide, aluminum hydroxide, aluminum nitride, boron nitride, zinc oxide, beryllium oxide, magnesium oxide and tin oxide. Desirably, component (C) is selected from any one of the group consisting of aluminum oxide, aluminum, zinc oxide, boron nitride, aluminum nitride and trihydrate aluminum oxide or any combination of more than one.
[0054] Component (C) is preferably a thermally conductive filler having an average particle size of 0.1 μm to 50 μm. Even more desirably, component (C) is selected from alumina particles having an average particle size of less than 5 μm, alumina particles having an average particle size of 5 μm or more, aluminum hydroxide particles having an average particle size of less than 5 μm, and aluminum hydroxide particles having an average particle size of 5 μm or more, or any combination of more than one filler. Using a laser diffraction particle size analyzer (CILAS920 particle size analyzer or Beckman Coulter LS13320SW), the average particle size of the filler particles is determined as the median particle size (D50) according to the operating software.
[0055] The content of component (C) is at least 90% by mass, preferably in the range of 90% to 95% by mass, relative to the total amount of the composition. This is because when the content of component (C) is equal to or greater than the lower limit of the above range, the thermal conductivity of the composition is good.
[0056] Component (D) is a polyether to provide a composition having excellent collapse resistance and vertical holding performance. Component (C) is at least one polyether selected from the group consisting of: (D1) polytetramethylene ether glycol (hereinafter "PTMEG"); (D2) alcohol-initiated copolymers of ethylene oxide and propylene oxide (hereinafter "alcohol-initiated EO / PO copolymers"); and (D3) polyether-modified organopolysiloxanes having no alkenyl group.
[0057] Component (D1) is generally polytetramethylene ether glycol represented by the following general formula:
[0058] H-(OCH2CH2CH2CH2) m –OH.
[0059] In the formula, m is a sufficient value to give PTMEG a molecular weight as described below. Specifically, m is preferably an integer satisfying the following conditions: 5≤m≤50, alternatively an integer satisfying the following conditions: 5≤m≤30, or, alternatively an integer satisfying the following conditions: 5≤m≤20.
[0060] Although the molecular weight of such PTMEG is not limited, the number average molecular weight (Mn) measured by gel permeation chromatography is preferably in the range of 300 to 3,000, or in the range of 300 to 2,500. This is because, if the number average molecular weight is higher than the lower limit of the above range, the dynamic physical properties of the obtained cured product will be good; however, on the other hand, if the number average molecular weight is lower than the upper limit of the above range, the applicability of the composition will be enhanced.
[0061] Component (D1) is commercially available as PTMEG 1000, PTMEG 1400 and PTMEG 2000 from Aladdin.
[0062] Component (D2) is typically an EO / PO copolymer initiated by an alcohol represented by the following general formula:
[0063] (A) z B
[0064] Where A represents HO-(C3H6-O) x -(C2H4-O) y -, wherein x is 8 to 40, y is 1 to 20; z is 1 to 12; and B is hydrogen or a monovalent hydrocarbon group, a divalent hydrocarbon group, or a polyvalent hydrocarbon group having 3 to 18 carbon atoms.
[0065] The sequence of ethylene oxide units (-C2H4-O-) and propylene oxide units (-C3H6-O-) in segment A may be random or may be oriented in any type of block configuration such as a single block of ethylene oxide units and a single block of propylene oxide units.
[0066] In the above formula, x and y are the average number of propylene oxide units and ethylene oxide units, respectively. The value of x may be 8 to 40, 10 to 35, 15 to 30, or 20 to 28. The value of y may be 1 to 20, 1 to 18, or 1 to 16.
[0067] In the above formula, z may be 1 to 12, 2 to 10, 3 to 8, or 4 to 6.
[0068] In the above formula, (x+y+z) has a value sufficient to give the alcohol initiated EO / PO copolymer a molecular weight as described below.
[0069] In the above formula, B may have 3 to 18 carbon atoms, 3 or 12 carbon atoms, 3 to 10 carbon atoms, 3 to 8 carbon atoms, or 4 to 6 carbon atoms. When B is a monovalent hydrocarbon group or a divalent hydrocarbon group, the alcohol-initiated EO / PO copolymer has a linear structure. When B is a polyvalent (e.g., trivalent or higher) hydrocarbon group, the alcohol-initiated EO / PO copolymer has a branched structure. B may be a group derived from sorbitol or a group derived from glycerol.
[0070] Alcohol-initiated EO / PO copolymers can be prepared from alcohol initiators having 3 or more carbon atoms, 4 or more carbon atoms, 5 or more carbon atoms, or even 6 or more carbon atoms, and at the same time typically 18 or less carbon atoms, 12 or less carbon atoms, 10 or less carbon atoms, 8 or less carbon atoms, or even 6 or less carbon atoms. The alcohol initiator can be a linear or branched alcohol, and preferably a branched alcohol. The alcohol initiator can be a monool, a diol, a triol, a tetraol, a pentanol, or a hexanol. Preferably, the alcohol initiator is hexanol. Preferably, the alcohol initiator used to prepare the EO / PO copolymer is sorbitol, glycerol, or a mixture thereof. Methods and conditions for preparing alcohol-initiated EO / PO copolymers are known to those skilled in the art, for example, at a temperature in the range of 20°C to 180°C or 100°C to 160°C. The preparation of alcohol-initiated EO / PO copolymers can be found, for example, in J. Herzberger et al., “Polymerization of ethylene oxide, propylene oxide, and other alkylene oxides: synthesis, novel polymer architectures, and bioconjugation,” Chemical Reviews, Vol. 116, No. 4, pp. 2170-2243 (2016).
[0071] By weight, the alcohol initiated EO / PO copolymer may comprise 50 mass % or more, 52 mass % or more, 55 mass % or more, 58 mass % or more, 60 mass % or more, 62 mass % or more, or even 65 mass % or more, while at the same time comprising propylene oxide units (also as propylene oxide chains) in an amount of 99 mass % or less, 98 mass % or less, 97 mass % or less, 96 mass % or less, or even 95 mass % or less, based on the weight of the alcohol initiated EO / PO copolymer.
[0072] Although the molecular weight of such component (D2) is not limited, it is preferred that the molecular weight is greater than 2,000 g / mol, for example, 2,100 g / mol or more, 2,200 g / mol or more, 2,300 g / mol or more, 2,500 g / mol or more, 2,600 g / mol or more, 2,700 g / mol or more, 2,800 g / mol or more, 2,900 g / mol or more, 3,000 g / mol or more, 3,200 g / mol or more, 3,500 g / mol or more, 3,800 g / mol or more, 4,000 g / mol or more, 4,500 g / mol or more, In some embodiments, the present invention relates to an aqueous solution of at least 200 g / mol and a mixture ... The molecular weight herein refers to the number average molecular weight (Mn) measured by gel permeation chromatography and is calculated by (56100*f) / OHV, wherein f represents the average number of hydroxyl groups per molecule of the alcohol-initiated EO / PO copolymer (also referred to as "OH functionality"), and OHV represents the hydroxyl value of the alcohol-initiated EO / PO copolymer in mg KOH / g as determined by ASTM D4274-2011. This is because if the number average molecular weight is higher than the lower limit of the above range, the dynamic physical properties of the obtained cured product will be good; however, on the other hand, if the number average molecular weight is lower than the upper limit of the above range, the applicability of the composition will be enhanced.
[0073] The polyether-modified organopolysiloxane used for component (D3) is not limited and can be any organopolysiloxane containing at least one polyether group. The polyether group of the polyether-modified organopolysiloxane can be a side group, a terminal group, or in both the side group position and the terminal group position. Component (D3) is generally a polyether-modified organopolysiloxane selected from a polyether-grafted organopolysiloxane or a block copolymer of a polyether and an organopolysiloxane. For example, the polyether group can be a part of the main chain of the polyether-modified organopolysiloxane. Alternatively or additionally, the main chain of the polyether-modified organopolysiloxane can contain only siloxane (Si-O-Si) bonds, or can contain divalent hydrocarbon linking groups, and other heteroatoms, such as O, N, and / or S. The polyether-modified organopolysiloxane can contain any combination of M, D, T and / or Q siloxy units. Typically, however, the polyether-modified organopolysiloxanes are linear and contain no branching due to T units and / or Q units.
[0074] Component (D3) is commercially available from Sigma-Aldrich.
[0075] The content of component (D) is in the range of 0.05% by mass to 5% by mass relative to the total amount of the composition. This is because when the content of component (D) is greater than or equal to the lower limit of the above range, the anti-collapse property and vertical holding property of the composition are improved, and when the content of component (D) is less than or equal to the upper limit of the above range, the stability of the composition is improved.
[0076] The addition of a curing agent renders the composition curable. If the composition is to be cured by a hydrosilylation reaction, such a curing agent is comprised of (E) an organopolysiloxane having at least two silicon-bonded hydrogen atoms per molecule and (F) a hydrosilylation reaction catalyst.
[0077] Component (E) is a crosslinking agent for component (A) in the composition and is an organopolysiloxane having at least two hydrogen atoms bonded to silicon atoms per molecule. In addition to hydrogen groups, examples of groups bonded to silicon atoms in component (E) include alkyl groups having 1 to 12 carbon atoms, such as methyl groups, ethyl groups, propyl groups, isopropyl groups, butyl groups, isobutyl groups, tert-butyl groups, pentyl groups, neopentyl groups, hexyl groups, cyclohexyl groups, heptyl groups, octyl groups, nonyl groups, decyl groups, undecyl groups, and dodecyl groups; aryl groups having 6 to 20 carbon atoms, such as phenyl groups, tolyl groups, xylyl groups, and naphthyl groups; aralkyl groups having 7 to 20 carbon atoms, such as benzyl groups, phenethyl groups, and phenylpropyl groups; and groups in which some or all of the hydrogen atoms in these groups are substituted by halogen atoms, such as fluorine atoms, chlorine atoms, or bromine atoms. In addition, the silicon atom in component (E) may also have a small amount of hydroxyl group or alkoxy group, such as methoxy group or ethoxy group, within the range not impairing the object of the present invention. However, the organopolysiloxane used for component (E) has neither a polyether group nor an alkenyl group in the molecule.
[0078] Examples of the molecular structure of component (E) include linear, partially branched linear, branched, cyclic, and three-dimensional network structures, and the molecular structure is preferably linear, partially branched linear, branched, or three-dimensional network structure.
[0079] Examples of such component (E) include methylhydrogenpolysiloxanes having both molecular ends capped with trimethylsiloxy groups; copolymers of dimethylsiloxane and methylhydrogensiloxane having both molecular ends capped with trimethylsiloxy groups; dimethylpolysiloxanes having both molecular ends capped with dimethylhydrogensiloxy groups; copolymers of dimethylsiloxane and methylhydrogensiloxane having both molecular ends capped with dimethylhydrogensiloxy groups; copolymers of methylhydrogensiloxane and diphenylsiloxane having both molecular ends capped with trimethylsiloxy groups; copolymers of methylhydrogensiloxane, diphenylsiloxane and dimethylsiloxane having both molecular ends capped with trimethylsiloxy groups; 1 / 2 Unit and SiO 4 / 2 Copolymer composed of (CH3)2HSiO 1 / 2 Unit, SiO 4 / 2 Unit and (C6H5)SiO 3 / 2 copolymers composed of such units; and mixtures of two or more types thereof.
[0080] The content of component (E) is to provide 0.5 mol to 5 mol, preferably 0.5 mol to 3 mol, alternatively 0.5 mol to 2 mol of hydrogen atoms bonded to silicon atoms relative to every 1 mol of alkenyl groups in component (A). This is because, when the content of component (E) is equal to or greater than the lower limit of the above range, the composition is fully cured. On the other hand, when the content of component (E) is equal to or less than the upper limit of the above range, the heat resistance of the cured product is enhanced.
[0081] Component (F) is a hydrosilylation catalyst that accelerates the curing of the composition. Examples of component (F) include platinum group element catalysts and platinum group element compound catalysts, and specific examples include platinum-based catalysts, rhodium-based catalysts, palladium-based catalysts, and combinations of at least two types thereof. In particular, platinum-based catalysts are preferred because the curing of the composition of the present invention can be significantly accelerated. Examples of these platinum-based catalysts include fine powdered platinum; platinum black; chloroplatinic acid, alcohol-modified chloroplatinic acid; chloroplatinic acid / diolefin complexes; platinum / olefin complexes; platinum / carbonyl complexes, such as platinum bis(acetoacetate) and platinum bis(acetylacetone); chloroplatinic acid / alkenyl siloxane complexes, such as chloroplatinic acid / divinyltetramethyldisiloxane complexes, and chloroplatinic acid / tetravinyltetramethylcyclotetrasiloxane complexes; platinum / alkenyl siloxane complexes, such as platinum / divinyltetramethyldisiloxane complexes and platinum / tetravinyltetramethylcyclotetrasiloxane complexes; complexes of chloroplatinic acid and acetylene alcohol; and mixtures of two or more types thereof. In particular, a platinum-alkenylsiloxane complex is preferable because curing of the composition can be accelerated.
[0082] Examples of alkenylsiloxanes used in the platinum-alkenylsiloxane complex include 1,3-divinyl-1,1,3,3-tetramethyldisiloxane, 1,3,5,7-tetramethyl-1,3,5,7-tetravinylcyclotetrasiloxane, alkenylsiloxane oligomers in which some methyl groups of the alkenylsiloxane are substituted with ethyl groups, phenyl groups, etc., and alkenylsiloxane oligomers in which vinyl groups of the alkenylsiloxane are substituted with allyl groups, hexenyl groups, etc. In particular, 1,3-divinyl-1,1,3,3-tetramethyldisiloxane is preferred because the stability of the resulting platinum-alkenylsiloxane complex is good.
[0083] To improve the stability of the platinum-alkenyl siloxane complexes, it is preferred that these platinum-alkenyl siloxane complexes be dissolved in alkenyl siloxane oligomers such as 1,3-divinyl-1,1,3,3-tetramethyldisiloxane, 1,3-diallyl-1,1,3,3-tetramethyldisiloxane, 1,3-divinyl-1,3-dimethyl-1,3-diphenyldisiloxane, 1,3-divinyl-1,1,3,3-tetraphenyldisiloxane or 1,3,5,7-tetramethyl-1,3,5,7-tetravinylcyclotetrasiloxane; or organosiloxane oligomers such as dimethylsiloxane oligomers, and it is particularly preferred that these complexes be dissolved in alkenyl siloxane oligomers.
[0084] The content of component (F) is a catalytic amount that accelerates the curing of the composition, but the content is preferably an amount of about 0.01 ppm to about 1,000 ppm of the platinum group metal in this component, measured in units of mass relative to this composition. In particular, the content is preferably an amount such that the content of the platinum group metal in component (F) is in the range of about 0.01 ppm to about 500 ppm, alternatively in the range of about 0.1 ppm to about 100 ppm, measured in units of mass relative to the composition. This is because when the content of component (F) is equal to or greater than the lower limit of the above range, the curability of the composition is good, and when the content of component (F) is equal to or less than the upper limit of the above range, the coloring of the cured product is suppressed, the cost of the composition is reduced, and the curing rate of the composition of the present invention can be controlled.
[0085] The composition may contain (G) a hydrosilylation reaction inhibitor for extending the usable time at ambient temperature and improving storage stability. Examples of component (G) include acetylenic alcohols such as 1-ethynyl-cyclohexan-1-ol, 2-methyl-3-butyn-2-ol, 2-phenyl-3-butyn-2-ol, 2-ethynyl-isopropan-2-ol, 2-ethynyl-butan-2-ol, and 3,5-dimethyl-1-hexyn-3-ol; silylated acetylenic alcohols such as trimethyl (3,5-dimethyl-1-hexyn-3-oxy) silane, dimethyl bis (3-methyl-1-butyn-oxy) silane, methyl vinyl bis (3-methyl-1-butyn-3-oxy) silane, and ((1,1-dimethyl-2-propynyl) oxy) trimethyl silane; unsaturated carboxylic acid esters such as diallyl maleate, maleic acid dimethyl ester, diethyl fumarate, diallyl fumarate and bis(2-methoxy-1-methylethyl)maleate, monooctyl maleate, monoisooctyl maleate, monoallyl maleate, monomethyl maleate, monoethyl fumarate, monoallyl fumarate and 2-methoxy-1-methylethyl maleate; enyne compounds such as 2-isobutyl-1-butene-3-yne, 3,5-dimethyl-3-hexene-1-yne, 3-methyl-3-pentene-1-yne, 3-methyl-3-hexene-1-yne, 1-ethynylcyclohexene, 3-ethyl-3-butene-1-yne and 3-phenyl-3-butene-1-yne; and mixtures of two or more types thereof.
[0086] The content of component (G) is not limited, as long as the content is an amount sufficient to control the curing speed of the composition. However, the content of component (G) is preferably an amount of about 0.001 to 5 parts by mass relative to 100 parts by mass of component (A), alternatively about 0.001 to about 2 parts by mass, or alternatively about 0.001 to about 1 part by mass. This is because when the content of component (G) is equal to or greater than the lower limit of the above range, the processing of the composition is good, and when the content of component (G) is equal to or less than the upper limit of the above range, the curability of the composition at low temperatures is good.
[0087] Component (H) is at least one filler treatment agent to help disperse component (C) in component (A). Component (H) is not limited, but it is preferably selected from the following filler treatment agents (H1) Organosiloxane represented by the following general formula (1):
[0088] R 1 3SiO(SiR 1 2O) a S i 1 b (OR 2 ) (4-b)
[0089] (H2) an alkoxysilane represented by the following general formula (2):
[0090] R 3 c R 4 d Si(OR 5 ) (4-c-d)
[0091] and mixtures of components (H1) and (H2).
[0092] In formula (1), each R 1 is independently an alkyl group having 1 to 3 carbon atoms or an alkenyl group having 2 to 6 carbon atoms. 1 Examples of the alkyl group of R include a methyl group, an ethyl group and a propyl group, among which a methyl group is preferred. 1 Examples of the alkenyl group include a vinyl group, an allyl group, a butenyl group, a pentenyl group and a hexenyl group, among which a vinyl group is preferred.
[0093] In formula (1), each R 2 is independently an alkyl group having 1 to 3 carbon atoms. 4 Examples of the alkyl group include a methyl group, an ethyl group and a propyl group, among which a methyl group is preferred.
[0094] In formula (1), a is an integer of 5 to 150, alternatively an integer of 10 to 120.
[0095] In formula (1), b is 0 or 1, and is preferably 0.
[0096] Examples of component (H1) include organosiloxanes represented by the following formula:
[0097] (CH3)3SiO[Si(CH3)2O] 20 Si(OCH3)3
[0098] (CH3)3SiO[Si(CH3)2O] 50 Si(OCH3)3
[0099] (CH3)3SiO[Si(CH3)2O] 110 Si(OCH3)3
[0100] (CH2=CH)(CH3)2SiO[Si(CH3)2O] 10 Si(OCH3)3
[0101] (CH2=CH)(CH3)2SiO[Si(CH3)2O] 20Si(OCH3)3
[0102] In formula (2), each R 3 is independently an alkyl group having 1 to 3 carbon atoms. 3 Examples of the alkyl group include a methyl group, an ethyl group and a propyl group, among which a methyl group is preferred.
[0103] In formula (2), each R 4 is independently an alkyl group having 6 to 12 carbon atoms. 4 Examples of the alkyl group include a hexyl group, a cyclohexyl group, a heptyl group, an octyl group, a nonyl group, a decyl group, an undecyl group, and a dodecyl group, among which an octyl group and a decyl group are preferred.
[0104] In formula (2), each R 5 is independently an alkyl group having 1 to 3 carbon atoms. 5 Examples of the alkyl group include a methyl group, an ethyl group and a propyl group, among which a methyl group is preferred.
[0105] In formula (2), c is 0 or 1, and d is 0 or 1, provided that c+d is 1 or 2.
[0106] Examples of alkoxysilanes for component (H2) include methyltrimethoxysilane, hexyltrimethoxysilane, heptyltrimethoxysilane, octyltriethoxysilane, decyltrimethoxysilane, dodecyltrimethoxysilane, dodecylmethyldimethoxysilane, dodecyltriethoxysilane, tetradecyltrimethoxysilane, octadecyltrimethoxysilane, octadecylmethyldimethoxysilane, octadecyltriethoxysilane, nonadecyltrimethoxysilane or any combination of at least two thereof.
[0107] The content of component (H) is not limited, as long as the content is enough to process the amount of component (C). However, the content of component (H) is preferably in the range of 0.1% by mass to 5% by mass of the composition, alternatively in the range of 0.1% by mass to 3% by mass, or alternatively in the range of 0.5% by mass to 3% by mass. This is because when the content of component (H) is equal to or greater than the lower limit of the above range, component (C) is fully surface treated to be loaded into the composition, and when the content of component (H) is equal to or less than the upper limit of the above range, the storage stability of the composition is good.
[0108] The composition of the present invention may further comprise (I) a pigment having the effect of maintaining the desired physical properties (i.e., appropriate softness and conformability) of the cured product of the composition. Examples of component (I) include red iron oxide, titanium white, carbon black, and phthalocyanine compounds. Of these, phthalocyanine compounds are preferred. Examples of phthalocyanine compounds include copper phthalocyanine and copper chloride phthalocyanine. Phthalocyanine compounds are commercially available from Alfa-Aesar.
[0109] The content of component (I) is not limited as long as it is an amount sufficient to maintain the desired physical properties. However, the content of component (I) is preferably an amount such that, based on mass units, the pigment is in the range of 0.01 to 5 parts by mass, alternatively in the range of 0.05 to 5 parts by mass, or alternatively in the range of 0.05 to 1 part by mass, relative to 100 parts by mass of component (A).
[0110] In addition, it is permissible to add a small amount of supplementary components to the composition of the present invention. Such auxiliary components are, for example, various fillers other than thermally conductive fillers and fumed silica fillers, antioxidants, dyes, heat stabilizers, adhesion promoters, flame retardants, plasticizers, etc.
[0111] Although the viscosity of the composition of the present invention at 25° C. is not limited, the viscosity is preferably 10,000 Pa·s or less, within a range of 500 Pa·s to 10,000 Pa·s, or within a range of 1,000 Pa·s to 10,000 Pa·s. This is because if the viscosity of the composition is higher than the lower limit of the above range, the mechanical properties of the obtained cured product will be good; however, on the other hand, if the viscosity is lower than the upper limit of the above range, the handleability of the obtained composition will be enhanced and air is less likely to be entrained in the cured product.
[0112] The composition can be prepared by uniformly mixing components (A) to (D), and if desired, any other components. When preparing the present composition, various types of mixers or kneaders can be used for mixing at normal temperatures, and if desired, can be mixed while heating. In addition, the order in which the various components are combined is not limited, and can be mixed in any order. In addition, the composition can be a one-part composition in which all components are blended in the same container, or can be a two-part composition mixed during use in view of storage stability.
[0113] Example
[0114] Hereinafter, the thermally conductive silicone composition of the present invention will be described in detail using Examples and Comparative Examples. However, the present invention is not limited by the description of the Examples listed below. The viscosity was measured at 25° C. In addition, in the Examples, measurements and evaluations were performed as described below.
[0115] <Thermal conductivity>
[0116] Thermal conductivity (W / m·K) was measured in accordance with ASTM D 5470 “Standard Test Method for Thermal Transmission Properties of Thermally Conductive Electrical Insulation Materials” using a thermal interface material (TIM) tester manufactured by LONGWIN instruments.
[0117] <allocation rate>
[0118] Load the thermally conductive silicone composition into a 30cc EFD plastic cartridge without a tip, then dispense the thermally conductive silicone composition at 90 psi (621 kPa) and record the weight of the composition dispensed within one minute. Repeat the test 5 times and record the average.
[0119] <Long tail observation>
[0120] After dispensing 5 small sample spots of approximately 0.15 mL, observe whether there is a long tail at the end and whether the tail is not easy to break. When the dispensing syringe is raised, check whether the material forms a tail. The sample spot has a total height of about 10 mm. If the total height of the sample spot is greater than 1.2 mm and the tail height is greater than 5 mm, it is recorded as a failure.
[0121] <Anti-collapse test>
[0122] Distribute 5 small sample points on the Al plate and measure the height and bottom length of the points. Place the Al plate horizontally for 24 hours. Observe the point shape and measure the height and bottom length of the points to calculate the aspect ratio of the points distributed. Calculate the slump trend (ST) value, which is the change in aspect ratio over a 24-hour period. If ST≤1.05, it can be marked as "no slump". If the value>1.05, it is marked as "slump".
[0123] The aspect ratio (AR) of the assigned sample point can be defined as the (height / diameter) of the specimen.
[0124] AR=h / d
[0125] The slump tendency (ST) of an assigned sample point can be defined as the ratio of the initial AR of the specimen to the AR of the specimen after a certain time.
[0126] ST=AR1 / AR2=(h1*d2) / (d1*h2)
[0127] If ST>1, it indicates that the sample has a tendency to collapse horizontally.
[0128] A higher ST value means a stronger collapse tendency.
[0129] <Vertical retention>
[0130] Distribute 5 sample points of 0.4 g and 1 g on the Al plate, respectively. Place the Al plate vertically for 24 hours, and observe whether the sample points stay in the original position.
[0131] <Viscosity and Thixotropic Index>
[0132] The viscosity at 25°C was measured by using an ARES G2 rheometer with the following conditions: 25 mm diameter serrated parallel plates; 1 mm gap; flow sweep mode; shear rates: 0.1 (1 / s) and 1 (1 / s) according to ASTM D 1084 "Standard Test Methods for Viscosity of Adhesives". The thixotropic index is given by the formula:
[0133] Thixotropic index = η(0.1) / η(1)
[0134] Where η(0.1) is the viscosity at a lower shear rate: 0.1 (1 / s), and η(1) is the viscosity at a higher shear rate: 1 (1 / s).
[0135] The following components were used to prepare the thermally conductive silicone compositions in Examples and Comparative Examples.
[0136] The following components were used as component (A).
[0137] V-P1: dimethyl polysiloxane, the dimethyl polysiloxane is represented by the following formula:
[0138] (CH2=CH)(CH3)2SiO-[Si(CH3)2O] 75 -Si(CH3)2(CH=CH2)
[0139] And the viscosity is 78mPa·s and the vinyl group content is 1.25% by mass
[0140] V-P2: dimethyl polysiloxane, the dimethyl polysiloxane is represented by the following formula:
[0141] (CH2=CH)(CH3)2SiO-[Si(CH3)2O] 380 -Si(CH3)2(CH=CH2)
[0142] And the viscosity is 2000mPa·s and the vinyl group content is 0.24 mass%
[0143] The following components were used as component (B).
[0144] Filler-1: BET specific surface area between 175m 2 / g to 225m 2 / g of hydrophobic fumed silica (AEROSIL 200V from Evonik)
[0145] The following components were used as component (C).
[0146] Filler-2: Spherical Al2O3 with an average particle size of 90 μm (purchased from Denka Company Limited in Japan under the name DAW-90)
[0147] Filler-3: Slightly rounded Al2O3 with an average particle size of 35 μm (purchased from Aluminum Corporation of China (Chialco) under the name A-SF-60)
[0148] Filler-4: irregular Al2O3 with an average particle size of 2 μm (purchased from Nippon Steel Sumikin Materials Co., Ltd. under the name AZ2-75)
[0149] Filler-5: ZnO with irregular particle size and average particle size of 0.11 μm to 0.13 μm (commercially available as Zoco 102 from Zochem)
[0150] Filler-6: platelet-shaped boron nitride filler with an average particle size of about 45 μm along the platelet and a platelet thickness between 5 μm and 10 μm (commercially available as PolarTherm PT110 from Momentive Performance Materials)
[0151] Filler-7: Spherical AlN with an average particle size of 80 μm (commercially available as ANF S-80ST204 from Maruwa Ceramic Co. Ltd. of Japan)
[0152] Filler-8: Spherical Al2O3 with an average particle size of 2 μm (known as ALUNABEADS TM CB-P02 is commercially available from Showa Denko Company)
[0153] The following components were used as component (H).
[0154] TA 1: n-Decyltrimethoxysilane (obtained from Gelest under the name SID2670.0)
[0155] TA 2: an organopolysiloxane represented by the following average formula:
[0156] (CH3)3SiO[(CH3)2SiO] 110 Si(OCH3)3
[0157] The following components were used as component (I).
[0158] Blue pigment: Copper phthalocyanine powder (CuPc) CAS 147-14-8 (40 wt%) dispersed in trimethyl terminated polydimethylsiloxane (200 fluid) (60 wt%) with a viscosity of 350 MPa.s by triple roll mill. α-Aesar catalog number 43650-09 and DOWSIL TM 200 fluid 350cSt
[0159] The following components were used as component (G).
[0160] Inhibitor: Methyl(tris(1,1-dimethyl-2-propynyloxy))silane (commercially available as ACM83817714 from Alfa Chemistry, 2200 Smithtown Avenue, Ronkonkoma, NY)
[0161] The following components were used as component (D).
[0162] Additive-1: PTMEG poly(tetramethylene ether glycol), Mn = about 1000 to about 2000) (commercially available as PTMEG 2000 from Aladdin)
[0163] Additive-2: EO-PO copolymer polyalkoxylate (propylene oxide = 94 mass %) containing ethylene oxide / propylene oxide block copolymer, alcohol alkoxylate initiated by sorbitol. The copolymer has an Mn of 9,600 g / mol, a viscosity of 13,400 mPa·s at 25°C, and an OHV of 30 to 36 mg KOH / g), where OHV represents the hydroxyl value of the alcohol alkoxylate as determined by ASTM D4274-2011 (as DOWFAX TM DF-162 nonionic surfactant commercially available from Dow
[0164] Additive-3: Polyether-grafted organopolysiloxane obtained by subjecting a copolymer of dimethylsiloxane and methylhydrogensiloxane to a hydrosilylation reaction with polyoxyethylene polyoxypropylene glycol monoacetate allyl ether (CAS 68037-64-9) (available from Sigma-Aldrich)
[0165] The following components were used as component (E).
[0166] XL 1: A copolymer of dimethylsiloxane and methylhydrogensiloxane terminated at both ends of the molecular chain with trimethylsiloxy groups, having a viscosity of 19 mPa·s, having 0.11 mol % SiH, and represented by the following average formula:
[0167] (CH3)3SiO[(CH3)2SiO] 25 [(CH3)HSiO]2Si(CH3)3
[0168] (Commercially available as HMS-071 from Galester)
[0169] The following components were used as component (F).
[0170] Pt 1: Platinum-divinyltetramethyldisiloxane complex (CAS 68478-92-2); 1.0% Pt in vinyl terminated PDMS (obtained from Galester)
[0171] [Examples IE1 to IE5 and Comparative Examples CE1 and CE2]
[0172] The thermally conductive silicone compositions shown in Table 1 were prepared using a 1 L Sigma paddle kneading mixer.
[0173] The specified amount of V-P1, V-P2, TA 1, TA2 and pigment are loaded into the mixer and mixed at 20 revolutions per minute (RPM) for 5 minutes under a nitrogen flow of 0.4 cubic meters per hour. Filler-1 and filler-5 are added, mixed at the same time and continued to mix at 45RPM for 10 minutes under a nitrogen purge. Filler-8 is added and mixed at 45RPM for 10 minutes under a nitrogen purge. Mixing is stopped and the material is scraped off the wall of the mixing container and the lid is covered. Filler-6 and filler-7 are added and mixed at 30RPM for 10 minutes under a nitrogen purge. Mixing is stopped and the material is scraped off the wall of the mixing container. Mixing is continued at 30RPM under vacuum and heated to 130°C for 40 minutes. Cool to 40°C, stop mixing and release vacuum. Scrape the material from the container wall and the mixer blade. Inhibitor, XL 1 and additives 1 to 3 are added and mixed at 30RPM for 15 minutes under a nitrogen purge, and then mixed for 15 minutes. Cool to 25°C, add Pt 1 to the mixer, mix at 30 RPM for 45 min under nitrogen purge. Continue mixing at 30 RPM for 20 min under full vacuum. Stop mixing and release vacuum to obtain a thermally conductive silicone composition for CE or IE.
[0174] [Table 1]
[0175]
[0176] The results from Examples IE1 to IE5 confirmed the following:
[0177] The total loading of fillers (AlN, BN, Al2O3, SiO2 and ZnO) was 95.83 wt%, so that these samples exhibited a thermal conductivity of 9.2 W / m·K. However, these samples exhibited excellent slump resistance and vertical retention.
[0178] The following were confirmed from the results of Comparative Examples CE1 and CE2:
[0179] The total loading of fillers (AlN, BN, Al2O3, SiO2, and ZnO) was 95.83 mass %, so that these samples exhibited thermal conductivity of 9.2 W / m·K or 9.3 W / m·K. However, these samples exhibited poor collapse resistance and poor vertical retention.
[0180] [Example IE6 and Comparative Examples CE3 and CE4]
[0181] The thermally conductive silicone compositions shown in Table 2 were prepared using a 4L Sigma paddle kneading mixer.
[0182] The specified amount of V-P1, V-P2, TA 1, TA 2 and pigment are loaded into the mixer and mixed for 5 minutes at 20 revs / min (RPM) under a nitrogen flow of 0.4 cubic meter / hour. Add filler-1 and filler-5, mix at the same time and continue mixing for 10 minutes at 45RPM under a nitrogen purge. Add filler-4, and mix for 10 minutes at 45RPM under a nitrogen purge. Stop mixing and scrape the material from the wall of the mixing container and cover it. Add filler-3, and mix for 10 minutes at 30RPM under a nitrogen purge. Add filler-2 and mix for 10 minutes at 30RPM under a nitrogen purge, stop mixing and scrape the material downward from the wall of the mixing container. Continue mixing at 30RPM under vacuum and heat to 130°C for 40 minutes. Cool to 40°C, stop mixing and release vacuum. Scrape the material from the container wall and the mixer blade. Add inhibitor, XL 1 and Additive-1 and mix at 30 RPM for 15 minutes under nitrogen purge, then mix for 15 minutes. Cool to 25°C, add Pt 1 to the mixer and mix at 30 RPM for 45 minutes under nitrogen purge. Continue mixing at 30 RPM for 20 minutes under full vacuum. Stop mixing and release vacuum to obtain a thermally conductive silicone composition for CE or IE.
[0183] [Table 2]
[0184]
[0185]
[0186] The following was confirmed from the results of Example IE6:
[0187] The total loading of fillers (Al2O3, SiO2 and ZnO) was 95.92 mass %, so that this sample exhibited a thermal conductivity of 6.2 W / m·K. However, this sample exhibited excellent collapse resistance and vertical retention.
[0188] The following was confirmed from the results of Comparative Examples CE3 and CE4:
[0189] The total loading of fillers (Al2O3, SiO2 and ZnO) for CE3 was 95.92 mass %, so that this sample exhibited a thermal conductivity of 6.2 W / m·K. However, this sample exhibited poor slump resistance and poor vertical retention.
[0190] The total loading of fillers (Al2O3, SiO2 and ZnO) for CE4 is also 95.92% by mass, so that this sample exhibits a thermal conductivity of 6.0 W / m·K. However, the tip of the dot still collapses easily, but it can remain in the original position during the vertical retention test. Due to the higher loading of nano-SiO2, the viscosity also increases a lot. The long tailing performance and lower dispensability cannot meet the requirements.
[0191] Industrial Applicability
[0192] Since the thermally conductive curable silicone composition of the present invention exhibits good shape retention properties and high thermal conductivity despite good processability and dispensability, the composition can be used as an encapsulant or potting material in electrical / electronic devices.
Claims
1. A thermally conductive silicone composition, comprising: (A) an organopolysiloxane having at least one alkenyl group having 2 to 12 carbon atoms per molecule and having a viscosity at 25° C. of 10 to 10,000 mPa·s; (B) hydrophobic fumed silica; (C) at least one thermally conductive filler; and (D) at least one polyether selected from the group consisting of: (D1) polytetramethylene ether glycol, (D2) alcohol-initiated copolymers of ethylene oxide and propylene oxide, and (D3) polyether-modified organopolysiloxanes; wherein the content of component (A) is in the range of 0.5% by mass to 5% by mass, the content of component (B) is in the range of 0.01% by mass to 0.5% by mass, the content of component (C) is at least 90% by mass, and the content of component (D) is in the range of 0.05% by mass to 5% by mass, respectively, relative to the total amount of the composition.
2. The thermally conductive silicone composition according to claim 1, wherein component (D1) is polytetramethylene ether glycol represented by the following general formula: H-(OCH2CH2CH2CH2) m –OH wherein m is an appropriate value giving the molecular weight of the polytetramethylene ether glycol a number average molecular weight (Mn) of 300 to 3,000 as measured by gel permeation chromatography. 3 . The thermally conductive silicone composition according to claim 1 , wherein component (D2) is an alcohol-initiated copolymer of ethylene oxide and propylene oxide, wherein the copolymer contains 50 to 99% by mass of propylene oxide units.
4. The thermally conductive silicone composition according to claim 1, wherein component (D3) is a polyether-modified organopolysiloxane selected from polyether-grafted organopolysiloxane or a block copolymer of a polyether and an organopolysiloxane.
5. The thermally conductive silicone composition according to claim 1, further comprising: (E) an organopolysiloxane having at least two silicon-bonded hydrogen atoms per molecule, the organopolysiloxane being present in an amount such that the silicon-bonded hydrogen atoms in component (E) are in the range of 0.1 mol to 5 mol per 1 mol of the alkenyl groups in component (A); and (F) a hydrosilylation reaction catalyst in an amount sufficient to promote the curing of the composition of the present invention.
6. The thermally conductive silicone composition according to claim 5, further comprising: (G) a hydrosilylation reaction inhibitor in an amount sufficient to control the curing speed of the composition.
7. The thermally conductive silicone composition according to claim 1, further comprising: (H) a filler treating agent in an amount sufficient to treat component (C).
8. The thermally conductive silicone composition according to claim 1, further comprising: (I) a pigment in an amount sufficient to maintain desired physical properties of the composition.
Citation Information
Patent Citations
Thermally conductive polysiloxane composition
US20200140736A1